Religious Fundamentalism in the Age of Pandemic - Käsehage, Nina (Religionswissenschaft, 2021)
The multidisciplinary anthology Religious Fundamentalism in the Age of Pandemic provides deep insights concerning the current impact of Covid-19 on various religious groups and believers around the world. Based on contributions of well-known scholars in the field of Religious Fundamentalism, the contributors offer about a window into the origins of religious fundamentalism and the development of these movements as well as the creation of the category itself. Further recommendations regarding specific (fundamentalist) religious groups and actors and their possible development within Buddhism, Christianity, Islam and Judaism round up the discussion about the rise of Religious Fundamentalism in the Age of Pandemic.